Synoptic to large‐scale drivers of minimum temperature variability in Australia – long‐term changes. (7th December 2017) - Crimp, Steven; Nicholls, Neville; Kokic, Philip; Risbey, James S.; Gobbett, David; Howden, Mark
ABSTRACT: This study documents the importance, and changes in the importance, of a suite of synoptic to large‐scale drivers of minimum temperature variability across the Australian region. The drivers investigated are the El Niño – Southern Oscillation (ENSO) as measured by the Southern Oscillation Index, atmospheric blocking, the Southern Annular Mode, and the position and intensity of the subtropical ridge. In most regions, individual drivers generally account for between about 5 and 10% of the interannual variability across Australia, although in some seasons and regions these drivers can collectively account for more than 60% of the observed variability. The amount of minimum temperature variance explained by individual drivers is highest in south‐eastern Australia in summer (December–February), where the drivers collectively account for 67% of the variance, due primarily to the relationships with blocking and ENSO. The varying importance of the drivers of minimum temperature variability between seasons and between two discrete periods (i.e. 1960–1984 and 1985–2015) has been investigated. In the more recent period the intensity of the subtropical ridge has played a more important role in minimum temperature variability, particularly in the south‐western and south‐eastern parts of Australia in summer (December–February), with the position of the subtropical ridge a feature of greater importance over much of Victoria in spring (September–November). For the more recent period the intensity of the subtropical ridge and the southern annular mode have been more important drivers of minimum temperature variability for autumn (March–May) and winter (June–August), respectively, across southern New South Wales and northern Victoria. Abstract : This study documents the importance, and changes in the importance, of a suite of synoptic to large‐scale drivers of minimum temperature variability across the Australian region, between seasons and two discrete periods. The drivers include El Niño Southern Oscillation (SOI), Blocking (BLK), Subtropical Ridge intensity and position (SRI and SRP) and the Southern Annular Mode (SAM). In the more recent period, the intensity of the subtropical ridge has played a more important role in minimum temperature variability.